Analisis Peramalan Obat Menggunakan Metode Simple Moving Average, Weighted Moving Average, Dan Exponential Smoothing - Briyan Gifari Aji; Dwi Chandra Aditya Sondawa; Fairuz Aqila Anindika; Dwi Januarita (STMIK Budi Darma, 2022)
Forecasting is one of the essential measures in decision making, especially for estimating the number of needs. Some large companies often hire consultants to analyze and advise on forecast product demand. Especially in the health sector, forecasting is needed to meet customer drug demand. In the last two years, the Healthy Prayer Clinic experienced problems in planning the procurement of non-generic drugs due to the COVID-19 pandemic, where the number of drug requests was greater than the number of available drug stocks. This happened because the Healthy Prayer Clinic ordered non-generic drugs without planning. This study aims to determine the demand for non-generic medications in the next period and provide recommendations for the best forecasting method to meet customer needs. The methods used in this research are Simple Moving Average (SMA), Weighted Moving Average (WMA), and Exponential Smoothing (ES). Then test the accuracy of forecasting using Mean Square Error (MSE), Mean Absolute Deviation (MAD), and Mean Absolute Percentage Error (MAPE). The results of the overall forecasting calculation using the Simple Moving Average method of 19.774, then the Weighted Moving Average method of 19.573, and the Exponential Smoothing method of 20.851. The results of the calculation of the best demand forecasting using the Exponential Smoothing (ES) method for 3 months carried out from April 2021 to April 2022 obtained results of 20.851 with forecasting error accuracy using Mean Square Error (MSE), Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE) is 1.341.137, respectively; 883; and 0.90%. The best method with the smallest accuracy rate for forecasting errors is the Exponential Smoothing method with forecasting values for the next month, April 2022, amounting to 20.851